2016
DOI: 10.1186/s12711-016-0254-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of selective sweeps reveals divergent selection between Chinese Holstein and Simmental cattle populations

Abstract: BackgroundThe identification of signals left by recent positive selection provides a feasible approach for targeting genomic variants that underlie complex traits and fitness. A better understanding of the selection mechanisms that occurred during the evolution of species can also be gained. In this study, we simultaneously detected the genome-wide footprints of recent positive selection that occurred within and between Chinese Holstein and Simmental populations, which have been subjected to artificial selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 52 publications
(78 reference statements)
2
28
0
1
Order By: Relevance
“…Only OAR6 harbored a large selected candidate region in both Latxa sheep populations, which constituted the major genomic difference with Sasi Ardi sheep. The absence of overlapping results between the different tests may be explained by their sensitivity to the different selection pressures [ 78 80 ]. Furthermore, a recent study that compared the performance of 11 different procedures for detecting selection signatures including Tajima’s D and F st reported low correlations [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only OAR6 harbored a large selected candidate region in both Latxa sheep populations, which constituted the major genomic difference with Sasi Ardi sheep. The absence of overlapping results between the different tests may be explained by their sensitivity to the different selection pressures [ 78 80 ]. Furthermore, a recent study that compared the performance of 11 different procedures for detecting selection signatures including Tajima’s D and F st reported low correlations [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Protein-coding and RNA genes mapped within the candidate regions, based on the UMD3.1 bovine reference genome annotation, were processed using the functional annotation tool implemented in DAVID Bioinformatics resources 6.7 to determine the over-represented (enriched) functional terms (Huang da et al, 2009a,b). An enrichment score of 1.3, which is equivalent to the Fisher exact test P = 0.05, was used as a threshold to define the significantly enriched functional terms in comparison to the whole bovine reference genome background.…”
Section: Methodsmentioning
confidence: 99%
“…Studies showed that two or more approaches combined can minimize the biases and false positives, as in the case of dairy cattle (Rothammer et al ) and Debao pony (Liu et al ). In this study, we applied three analytical methods ( F ST , XP‐EHH and XP‐CLR) to identify candidate genes related to heat tolerance and disease resistance in DHH, and found that no gene was detected by above‐mentioned three methods, which is mainly attributed to the different characteristics of these methods (Chen et al ). Nonetheless, 15 of 28 common genes were associated with heat tolerance and disease resistance (Table and Table ) in our study.…”
Section: The Candidate Genes Are Associated With Heat Tolerance and Imentioning
confidence: 99%